Teknik Peningkatan Kesuburan Lahan Berpasir Dengan Perlakuan Pupuk Kandang Ayam Pada Budidaya Kacang Tanah - Saijo Saijo (Bioscientiae, 2022)
The study aimed to analyze the effective dose of chicken manure in the peanut cultivation using sandy soil. The data were analysed by a one-factor randomized block design with 4 levels repeated 4 times, therefore that 16 experimental units were obtained. The treatment dose level was in the form of fertilizer, sometimes chicken. The variables observed were: plant height (cm), number of wet pods planted (pods), weight of wet pods planted (g), weight of dry pods planted (g), number of seeds planted (seeds) and weight of dry seeds planted (g). The result showed treatment of chicken manure dose at a dose of 15 t ha-1 (A3) gave a very significant effect on all plant height variables. Treatment dose of manure 5 t ha-1 also had a significant effect on yield variables in the form of number of pods, wet pod weight, and dry pod weight. The most effective doses were 10 t ha-1 (A2) and 15 t ha-1 (A3). In addition, the variable number of seeds and dry seed weight of treated pods at a dose of 10 t ha-1 (A2) gave the highest number of seed pods at 76.50 seeds plant-1 and the heaviest pod dry weight was 45.06 g plant-1.